The effectiveness of Islamic education management: a study at Ummul Mukminin Islamic Boarding School for Female, Makassar - Kahadiah, Kahadiah; Muslimin, Abdul Azis; Malli, Rusli (TARBAWY: Indonesian Journal of Islamic Education, 2023)
The purpose of this study was to analyze the effectiveness of Islamic education, to analyze the management of character building for students, and to analyze the inhibiting factors for the effectiveness of Islamic education for the management of character development for students at Ummul Mukminin Putri Islamic Boarding School, Makassar City. This qualitative research uses the descriptive analysis method. The results of the study show that the effectiveness of Islamic education is realized in the pesantren coaching system, which refers to the concept of Islamic education, and all the substance of Islamic education is taught by all subject teachers to the students at Ummul Mukminin Putri Islamic Boarding school. The Management of Character Development at the Ummul Mukminin Putri Islamic Boarding School is internalized into several things.Tujuan penelitian ini adalah untuk menganalisis efektivitas pendidikan Islam, menganalisis manajemen pembentukan karakter santri, dan menganalisis faktor-faktor penghambat efektivitas pendidikan Islam terhadap manajemen pengembangan karakter santri di Pondok Pesantren Ummul Mukminin Putri. Sekolah, Kota Makassar. Penelitian kualitatif ini menggunakan metode deskriptif analisis. Hasil penelitian menunjukkan bahwa efektivitas pendidikan Islam diwujudkan dalam sistem pembinaan pesantren yang mengacu pada konsep pendidikan Islam, dan seluruh substansi pendidikan Islam diajarkan oleh seluruh guru mata pelajaran kepada santri di Ummul Mukminin Putri Islam. Sekolah Berasrama. Manajemen Pembinaan Karakter di Pondok Pesantren Ummul Mukminin Putri diinternalisasikan ke dalam beberapa hal.